A novel mechanism for improvement of dry skin by dietary milk phospholipids: Effect on epidermal covalently bound ceramides and skin inflammation in hairless mice. Issue 3 (June 2015) - Morifuji, Masashi; Oba, Chisato; Ichikawa, Satomi; Ito, Kyoko; Kawahata, Keiko; Asami, Yukio; Ikegami, Shuji; Itoh, Hiroyuki; Sugawara, Tatsuya
Highlights: Dietary milk phospholipids improved dry skin conditions in hairless mice. Milk phospholipids attenuated a decrease in epidermal protein-bound ω-hydroxy ceramide levels. Milk phospholipids lowered levels of skin and serum markers of inflammation. Abstract: Background: Dietary milk phospholipids (MPLs) increase hydration of the stratum corneum and reduced transepidermal water loss (TEWL) in hairless mice fed a standard diet. However, the mechanism by which MPLs improve skin barrier functions has yet to be established. Objective: This study was designed to examine the mechanism by which MPLs may affect covalently bound ceramides and markers of skin inflammation and improve the skin barrier defect in hairless mice fed a magnesium-deficient (HR-AD) diet. Methods: Four-week-old female hairless mice were randomized into four groups ( n = 10/group), and fed a standard (control) diet, the HR-AD diet, the HR-AD diet supplemented with either 7.0 g/kg MPLs (low [L]-MPL) or 41.0 g/kg MPLs (high [H]-MPL). Results: Dietary MPLs improved the dry skin condition of hairless mice fed the HR-AD diet. MPLs significantly increased the percentage of covalently bound ω-hydroxy ceramides in the epidermis, and significantly decreased both thymus and activation-regulated chemokine (TARC) mRNA and thymic stromal lymphopoietin (TSLP) mRNA levels in skin, compared with the HR-AD diet. Furthermore, the MPL diets significantly decreased serum concentrations of immunoglobulin-E, TARC, TSLP, and soluble P-selectin versus the HR-AD diet. Conclusion: Our study showed for the first time that dietary MPLs may modulate epidermal covalently bound ceramides associated with formation of lamellar structures and suppress skin inflammation, resulting in improved skin barrier function.